2017
DOI: 10.1111/ijd.13454
|View full text |Cite
|
Sign up to set email alerts
|

Regression of cutaneous xerosis with emollient treatment in sub‐Saharan African patients

Abstract: Emollients have proven effective in improving cutaneous xerosis in various populations; however, no clinical data are available for African patients. The observational study "Xerafrica" was conducted by dermatologists in seven sub-Saharan countries to assess the evolution of xerosis after an 8-week treatment with an emollient. Patients were children above 3 years or adults. Secondary objectives were to assess pruritus, improvement in symptoms, quality of life, satisfaction, and tolerance. An analysis of 185 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This improvement in DLQI scores is of particular interest given that the results of previous studies did not always show improvement in clinical symptoms correlating to significant improvements in QoL scores [39,40]. However, improvements in QoL after emollient use have been demonstrated in some studies, including that by Boralevi et al [30] in adult African patients.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This improvement in DLQI scores is of particular interest given that the results of previous studies did not always show improvement in clinical symptoms correlating to significant improvements in QoL scores [39,40]. However, improvements in QoL after emollient use have been demonstrated in some studies, including that by Boralevi et al [30] in adult African patients.…”
Section: Discussionmentioning
confidence: 84%
“…b Slightly greater improvements in both scores were observed for patients in the concomitant subpopulation who used the study product in the form of a balm compared to those using the cream (sleep disturbance: -2.3 balm vs -1.9 cream, p = 0.07; DLQI: -6.3 balm vs -6 cream, p = 0.18) associated with a range of dermatoses, including atopic dermatitis [24][25][26], xerosis associated with chronic pruritus in elderly patients [27], mild-to-moderate plaque psoriasis [28], and foot xerosis [29]. Finally, in the first study of its kind to evaluate the effects of emollients on xerosis and pruritus in an African population, an 8-week regimen with a glycerol-based emollient was shown to lead to 80% reductions in xerosis severity in adults and children, and to 40% and 80% reductions in pruritus severity in adults and children, respectively [30]. However, around 41% of the patients in the study by Boralevi et al [30] were also prescribed another topical treatment (most commonly a topical steroid) at inclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in recent years, an increasing number of studies have investigated the benefits of skin care products, such as emollients or creams, on the management of cutaneous AEs in various populations, including oncology patients [26][27][28][29]. A realworld study in an African population showed that an 8-week regimen with a glycerol-based emollient could lead to reductions in xerosis severity of more than 80% in adults and children, with the effects starting to be observed within the first 4 weeks of treatment [30]. The authors also reported improvements in QoL related to this skin condition.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous xerosis presents itself as a modification of the stratum corneum characterized by impaired proliferation and differentiation of keratinocytes, lipid content, hydration, pH and sebum production. Thus, it affects the skin barrier function and results in skin discomfort and aesthetic concerns, and the treatment is usually topical and symptomatic with emollients or keratolytics (2) .…”
Section: Introductionmentioning
confidence: 99%